Transverse distributed coupling between specifically terminated low loss VLSI interconnections - Özkaramanli, H (IEEE, 2000)
Crosstalk and signal propagation on low loss coupled VLSI interconnects with specific terminations are analyzed and a modulation type behavior where voltage waves on the two interconnects oscillate almost periodically is described. The quasiperiod of the envelope is determined in terms of the even and odd mode one way propagation times. The modulation type behaviour is a characteristic of coupled lines with fast drivers and low loss interconnects. The amplitude of the crosstalk signals are shown to reach as high as the excitation signals amplitude.
IEEE International Symposium on Circuits and Systems (ISCAS 2000) -- MAY 28-31, 2000 -- GENEVA, SWITZERLAND
Keywords: Lines